T-type calcium channel modulation by hydrogen sulfide in neuropathic pain conditions - Rangel-Galván, Maricruz; Rangel-Galván, Violeta; Rangel-Huerta, Alejandro (Frontiers in Pharmacology, 2023)
Neuropathic pain can appear as a direct or indirect nerve damage lesion or disease that affects the somatosensory nervous system. If the neurons are damaged or indirectly stimulated, immune cells contribute significantly to inflammatory and neuropathic pain. After nerve injury, peripheral macrophages/spinal microglia accumulate around damaged neurons, producing endogenous hydrogen sulfide (H2S) through the cystathionine-γ-lyase (CSE) enzyme. H2S has a pronociceptive modulation on the Cav3.2 subtype, the predominant Cav3 isoform involved in pain processes. The present review provides relevant information about H2S modulation on the Cav3.2 T-type channels in neuropathic pain conditions. We have discussed that the dual effect of H2S on T-type channels is concentration-dependent, that is, an inhibitory effect is seen at low concentrations of 10 µM and an augmentation effect on T-current at 100 µM. The modulation mechanism of the Cav3.2 channel by H2S involves the direct participation of the redox/Zn2+ affinity site located in the His191 in the extracellular loop of domain I of the channel, involving a group of extracellular cysteines, comprising C114, C123, C128, and C1333, that can modify the local redox environment. The indirect interaction pathways involve the regulation of the Cav3.2 channel through cytokines, kinases, and post-translational regulators of channel expression. The findings conclude that the CSE/H2S/Cav3.2 pathway could be a promising therapeutic target for neuropathic pain disorders.